2018
DOI: 10.1007/s00234-018-2022-4
|View full text |Cite|
|
Sign up to set email alerts
|

Does stent type impact coil embolization outcomes in extended follow-up of small-sized aneurysms (< 10 mm)?

Abstract: Above findings demonstrate that in addition to occlusive status at time of coil embolization and neck size, stent type may affect follow-up outcomes of stent-assisted coil embolization in small-sized aneurysms. LVIS (vs Enterprise or Neuroform stents) performed best during follow-up monitoring in terms of limiting recanalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 57 publications
2
4
0
Order By: Relevance
“…These findings may provide some reference for treatment decisions of a multi-disciplinary team. It has been identified that the size of intracranial aneurysms significantly affects the selection and treatment effectiveness of intracranial aneurysms (32)(33)(34)(35). Consistently, our analysis showed that intracranial aneurysms of size > 7 mm have a significantly higher risk of recurrence after coil embolization.…”
Section: Discussionsupporting
confidence: 86%
“…These findings may provide some reference for treatment decisions of a multi-disciplinary team. It has been identified that the size of intracranial aneurysms significantly affects the selection and treatment effectiveness of intracranial aneurysms (32)(33)(34)(35). Consistently, our analysis showed that intracranial aneurysms of size > 7 mm have a significantly higher risk of recurrence after coil embolization.…”
Section: Discussionsupporting
confidence: 86%
“…The current study found that laser engraved stent-assisted embolization had a high deployment success rate and fewer periprocedural intracranial hemorrhage rates than braided stent-assisted embolization. Deployment and the follow-up results of the current study are in line with the results of the retrospective review study, 14 multi-center analysis, 15 and comparison studies. 10 13 17 18 Laser engraved stent has technical feasibility in applying stent-through compared to a braided stent in the procedure of stent-assisted coil embolization.…”
Section: Discussionsupporting
confidence: 84%
“… 13 For small-sized intracranial aneurysms (< 10 mm) among Korean patients, braided stents with closed cells have favorable postoperative outcomes as compared to open-cell or laser-cut stents. 14 Also, laser-cut stents have a higher rate of successful deployment and lower events of periprocedural intracranial hemorrhage. 13 Efficacy and safety analysis of braided stent and laser engraved stent in coil embolization among Chinese patients with complex intracranial aneurysms are not been adequately investigated yet 10 15 and there are still controversies regarding the effects of the braided stent and laser engraved stent in coil embolization because both are closed type stents.…”
Section: Introductionmentioning
confidence: 99%
“…This rate was lower than the rate of 90.5% in our study. Lee et al reported 312 small-sized aneurysms (<10 mm) treated with different stents, in which the aneurysm recanalization rate after LVIS stenting was 6.5%; a much lower rate than with the Enterprise (18.2%) and Neuroform stents (29.6%) (22). Using the compression technique to release the stent requires skillful operation experience.…”
Section: Lvis Stents and The Compressed Stent Techniquementioning
confidence: 99%